Sources of financing the activities promoting sport and physical education on the basis of the example of Polish foundations and associations = Źródła finansowania działań promujących sport i wychowanie fizyczne na przykładzie polskich fundacji i stowarzyszeń - Mamcarczyk, Mariola; Zieniuk, Paweł (Zielona Góra: Faculty of Economics and Management Press)
At present 177 thousand associations and 26 thousand foundations operate in Poland, which are involved in many different areas of public benefit activities and finance their activities from various sources. The paper presents the results of own studies carried out on a sample of 100 public benefit organisations conducting activity in the area of supporting and promoting physical education and sport.
Keywords: public benefit organizations; foundations; associations; sport; physical education; organizacja pożytku publicznego; Fundacja; stowarzyszenia; wychowanie fizyczne